RELIGION, POPULAR CULTURE, AND FASHION: NEGOTIATING ISLAMIC ETHICS AMONG GEN Z STUDENTS IN KUDUS - Shafiya Noor Hasna; Moh Muhtador (Institut Agama Islam Negeri (IAIN) Curup, 2026)
The phenomenon of fashion and the existence of Outfit of the Day (OOTD) as a digital pop culture trend has influenced the way Generation Z Muslim students dress, including in religious and social contexts such as Kudus. Amid the dominance of social media as a source of visual references, students' dressing practices are no longer understood solely as a fulfillment of neatness and academic formality, but also as a space where popular aesthetic demands and Islamic ethical values intersect. This study aims to analyze how Generation Z Muslim students in Kudus respond to the influence of the OOTD phenomenon in their daily dressing practices and how Islamic ethics play a role in the process of selecting and limiting this influence. This study uses a descriptive-analytical qualitative approach through observation of student dressing practices on campus and semi-structured interviews with a number of students. Data analysis was carried out using Islamic ethics as the main analytical framework, particularly the concepts of aurat, modesty (ḥayā’), and moral responsibility for the body. The results show that students do not directly imitate OOTD references, but rather adopt cuts, silhouettes, and styles of dress that are considered “neat” and “up-to-date.” However, in practice, this tendency often blurs the boundaries of Islamic dress ethics. This study confirms that student dressing practices are a continuous negotiation between digital aesthetics and Islamic ethics. Academically, this study contributes as an empirical reference in contemporary Islamic ethics studies, particularly in reading the dynamics of Muslim student dressing in the era of digital popular culture.